G448 Juvenile dermatomyositis associated with interstitial lung disease: would anti-mda5 antibody detection improve early diagnosis and management?. (12th March 2018) - Gallagher, K; Bale, P; Armon, K
Abstract : Aims: We describe a case of anti-MDA5 antibody positive Juvenile Dermatomyositis(JDM) associated with interstitial lung disease(ILD) and propose early antibody detection may guide management and improve outcome. Methods: A 15-year-old male presented with a 3 month history of pain and stiffness in his right ankle, left knee and hand joints associated with mild weakness. A blistering rash on his extremities developed into classical JDM facial rash with periorbital swelling, Gottron papules and paranychial ulcers. Initial investigations included: EMG study showing myopathy; MRI buttock and skin biopsy both consistent with dermatomyositis (see table 1). He started hydroxychloroquine, weekly methotrexate injections and high dose prednisolone including fortnightly 3 day intravenous pulses. Results: Within one month, he developed a knee staphylococcus aureus arthritis which required prolonged antibiotics. Despite minimal respiratory symptoms, his lung function test showed a restrictive pattern with reduced diffusion(FVC-7.57 predicted, TLC-4.18, DLC −2.2). ILD with patchy consolidation was confirmed on imaging. IV immunoglobulins(IVIG) were added. Two weeks later, he developed chest pain and shortness of breath, with clinical signs of surgical emphysema confirmed radiologically, with apical pneumothoraces, pneumomediastinum and pneumopericardium. The air leaks were secondary to bronchial perforations secondary to JDM related ILD. Although the rash, arthritis and myositis responded to treatment, his ILD progressed. He required admission to PICU for respiratory support and was covered for infection including pneumocystis pneumonia. Further IVIG and IV methylprednisolone was given and mycophenolate commenced. However, his deterioration necessitated ventilation and transfer for ECMO. His bloods showed anti-MDA5 positive antibodies. Plasmapheresis, cyclophosphamide and rituximab were given but despite best efforts, he died from ILD secondary to JDM. Conclusion: Anti-MDA5 antibodies have been reported in rapidly progressive ILD associated with JDM. Despite the usual manifestations responding to treatment, his lung disease was unremittingly progressive. The clinical features associated with this rare form included the unusual vasculitic lesions periungually and on the palms/soles. At diagnosis, we recommend requesting full myositis-specific antibodies including anti-MDA5 which may help guide management. The advent of aggressive staphylococcus auerus arthritis delayed the use of additional immunosuppressants once ILD was diagnosed and IVIG was used whilst treating the infection. Early aggressive immunosuppression is recommended.